(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Recent decades have revealed a signifcant change in the eating behavior and lifestyle of adolescents. These changes are mainly observed in the increasing consumption of highcalorie foods and sweet drinks, as well as in a more sedentary lifestyle and a signifcant lack of exercise approximately 2 years—during the COVID-19 pandemic— have only intensifed this unfavorable behavior [2].The National Kidney Foundation published the Kidney Disease Outcomes Quality Initiative (K/DOQI) clinical practice guidelines for CKD in 2001.